Allometry and morphological integration in the skull of Tupinambis merianae (Lacertilia: Teiidae) - Monteiro, Leandro R. [UNESP]; Abe, Augusto Shinya [UNESP] (De Gruyter, 1997)
The morphogenetic processes acting in the skull of the lizard Tupinambis merianae were investigated by geometric morphometric techniques. The observed ontogenetic shape change involved a widening of the anterior extremity, stretching and narrowing of the midface, narrowing of the braincase, orbital reduction and elongation of the temporal region (origin of jaw adductor muscles). This change occurred mostly in a localized way in certain cranial regions. The major components identified were: rostrum, midface, dermal elements of braincase (functionally influenced) and endochondral elements of braincase (embryologically influenced). The growth patterns lead to an increased robustness of the skull (particularly the anterior extremity) and a reduction of cranial kinesis. These changes, together with the ontogenetic variation in dentition aid in the ontogenetic variation observed in the diet of these animals, which shift from carnivory to omnivory.